Penanganan Stroke Iskemik Akut di Masa Pandemi COVID-19 - Lengkong, Erlika; Warouw, Finny; Kembuan, Mieke A. H. N. (Universitas Sam Ratulangi, 2021)
Abstract: When the pandemic corona virus disease (COVID-19) occurs, emergency services and hospitals are finally disrupted. One of the medical emergencies which can cause death and disability as well as other problems if being ignored, especially in productive age patients is stroke. This study was aimed to obtain the management of ischemic stroke during COVID-19 pandemic. This was a literature review study using three databases, namely Clinical Key, PubMed and Google Scholar. The keywords used in data search were acute AND stroke AND pandemic. The results showed that the treatment of acute ischemic stroke during COVID-19 pandemic consisted of three stages, namely pre-hospitalization (public education, contacting medical assistance, use of personal protective equipment, pre-notification), hospitalization (emergency room, imaging room, neuroradiology unit, ICU and IMCU), and post hospitalali-zation (integrated team approach). In conclusion, the management of acute ischemic stroke during COVID-19 pandemic begins before the medical personnel take action until the action is carried out. The main things in the management of acute ischemic stroke during COVID-19 pandemic are handling fast and precisely, using adequate personal protective equipment (PPE), and using communication tools or long-distance medical care (telemedicine).Keywords: acute ischemic stroke, COVID-19, pandemicÂ Abstrak: Saat terjadi pandemi corona virus disease (COVID-19), layanan kegawatdaruratan dan rumah sakit megalami perubahan. Salah satu kasus kegawatdaruratan medik yang menjadi penyebab kematian dan kecacatan serta dapat menimbulkan masalah lainnya jika diabaikan terutama pada pasien usia produktif ialah stroke. Penelitian ini bertujuan untuk mengetahui penanganan stroke pada masa pandemic COVID-19. Jenis penelitian ialah literature review yang menggunakan tiga database yaitu Clinikal key, PubMed dan Google Scholar. Kata kunci yang digunakan dalam pencarian data ialah acute AND stroke AND pandemic. Hasil penelitian mendapatkan penanganan stroke iskemik akut di masa pandemi COVID-19 terdiri dari 3 tahapan yakni prahospitalisasi (edukasi masyarakat, menghubungi bantuan medis, penggunaan alat pelindung diri, pranotifikasi rumah sakit), hospitalisasi (ruang gawat darurat, ruang pencitraan, unit neuroradiologi, ICU dan IMCU), dan pasca hospitalisasi (pendekatan tim terpadu). Simpulan penelitian ini ialah penanganan stroke iskemik akut di masa pandemi COVID-19 dimulai dari sebelum tenaga medis melakukan tindakan sampai setelah tindakan dilaksanakan. Hal utama dalam penanganan stroke iskemik akut di masa pandemi COVID-19 ialah penanganan yang cepat dan tepat, penggunaan alat pelindung diri (APD) yang memadai, dan pemanfaatan alat komunikasi atau perawatan medis jarak jauh.Kata kunci: stroke iskemik akut, pandemi, COVID-19